2014
DOI: 10.1186/1479-5868-11-59
|View full text |Cite
|
Sign up to set email alerts
|

The value of (pre)school playgrounds for children’s physical activity level: a systematic review

Abstract: The (pre)school environment is an important setting to improve children’s health. Especially, the (pre)school playground provides a major opportunity to intervene. This review presents an overview of the existing evidence on the value of both school and preschool playgrounds on children’s health in terms of physical activity, cognitive and social outcomes. In addition, we aimed to identify which playground characteristics are the strongest correlates of beneficial effects and for which subgroups of children ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 63 publications
2
98
2
2
Order By: Relevance
“…Playgrounds are places specifically developed to offer opportunities for children to play and be physically active, thus facilitating healthy development (Broekhuizen et al 2014). With various play equipment and play areas, they provide affordances that do not necessarily cause children’s activities, but which offer action possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Playgrounds are places specifically developed to offer opportunities for children to play and be physically active, thus facilitating healthy development (Broekhuizen et al 2014). With various play equipment and play areas, they provide affordances that do not necessarily cause children’s activities, but which offer action possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…With various play equipment and play areas, they provide affordances that do not necessarily cause children’s activities, but which offer action possibilities. Broekhuizen et al (2014) conducted a systematic review of the value of (pre-)school playgrounds on children’s physical activity levels and found positive associations between provision of (portable and fixed) play equipment, playground size and decreased playground density (children per square meter) on physical activity in school children. In another review, the contribution of playground designs to increasing physical activity levels was also investigated in a school setting and showed that playground markings plus physical structures increase physical activity during recess (Escalante et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, one systematic review reported that there was inconclusive evidence for positive effects of playground interventions in the school setting on children's physical activity levels. 20 Therefore, in this study, we aimed to determine whether there was an association between SES and MVPA participation in Australian schoolchildren aged 9 to 11 years, and whether school facilities, sports, or policies relating to physical activity contributed to these gradients. There were 3 research questions for this study:…”
mentioning
confidence: 99%
“…Nor did we find information about the impact of playing in natural environments on gross motor skill development. With a growing literature highlighting the short [29,30,31] and longer-term importance of motor skill development [32] and a child’s micro environment to PA (particularly school grounds) [33,34,35], as well as the importance of exposure to nature to mental and physical well-being [36], we felt it was important to determine whether children were being exposed to natural features at their elementary schools and to assess whether these natural features afforded opportunities for motor skill development. …”
Section: Discussionmentioning
confidence: 99%